Pemanfaatan Instagram sebagai Media Informasi Pariwisata pada Akun @hutanpinuslimpakuwuss - Rena Kus Daniningsih; Dhety Chusumastuti (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Hutan Pinus Limpakuwus is one of nature tourism with a family-friendly concept located in Banyumas, Central Java. In carrying out its activities, Hutan Pinus Limpakuwus tourism utilizes several social media, one of which is Instagram. This study aims to find out how to use Instagram @hutanpinuslimpakuwuss social media through the share, optimize, manage and engage stages. This study used the descriptive qualitative method. Data collection techniques used are observation, interviews, and documentation. From the results of the study, it is known that the use of the content on social media Instagram @hutanpinuslimpakuwuss at the sharing stage begins with determining and understanding the target audience for the Hutan Pinus Limpakuwus tourism. At the optimization stage, observations are made on the current trend by utilizing the hashtag feature. At the managed stage, evaluate through the insight feature and make a schedule for uploading content. At the engagement stage, it is done by establishing relationships with information provider accounts in Banyumas and its surroundings to increase exposure. The use of social media itself has a relationship with the dissemination of information. Keywords : Social Media, Instagram, Information Medium, Tourism, Hutan Pinus